A Minor Calculation On Co-Prime Knots And Links For p, q ≤ 20 - Salih, Hero Mawlood; Shareef, Hardi Ali; Aziz, Hardi Nasradeen (Sulaimani Journal for Pure and Applied Sciences, 2024)
A knot K is a prime knot if it is not the unknot, in this paper, we present a novel classification of coprime knots and links, leveraging the calculus of continued fractions. Additionally, we provide an illustrative depiction of these coprime structures utilizing the SnapPy program, thereby obtaining crucial insights into their properties. The last section of this article presents a detailed table showing various knots and links, and their respective volumes, Schubert presentations with other important informations about them. So our investigation focuses on the coprime digits of knots, specifically those knots and links that are associated with the set of prime numbers from 1 to 20.
Keywords: Knots; Hyperbolic geometry; Hyperbolic Co volume Schubert presentation